2009
DOI: 10.1590/s0031-10492009003500001
|View full text |Cite
|
Sign up to set email alerts
|

Avifauna da Estação Ecológica dos Caetetus, interior de São Paulo, Brasil

Abstract: A Estação Ecológica dos Caetetus possui um dos maiores remanescentes de mata estacional semidecídua ainda presentes no Estado de São Paulo. Poucos estudos foram realizados nessa localidade, extremamente importante no que diz respeito às aves da Mata Atlântica do interior do Estado. Para caracterizar a avifauna da estação com dados recentes e contribuir com novos registros, foi realizado um levantamento da avifauna utilizando-se o método de Pontos de Escuta entre outubro de 2005 e dezembro de 2006. Foram regist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…Because we studied smaller (five landscapes of 16 km 2 ) and highly deforested (11% forest cover) landscapes, and we observed only one high-sensitivity species according to Parker, we believe that higher richness of Parker's high-sensitivity species are primarily found in less deforested and impacted landscapes. Other studies performed in larger and protected Atlantic Forest patches also found elevated richness of high-sensitivity species, corroborating our assumption (e.g., more than 15 forest high-sensitivity species were reported in Develey and Martensen, 2006;Cavarzere et al, 2009;Antunes et al, 2013). This condition may explain the lack of relationship between Parker's high-sensitivity species and the variation of forest environmental conditions in more disturbed landscapes.…”
Section: Localsupporting
confidence: 90%
See 1 more Smart Citation
“…Because we studied smaller (five landscapes of 16 km 2 ) and highly deforested (11% forest cover) landscapes, and we observed only one high-sensitivity species according to Parker, we believe that higher richness of Parker's high-sensitivity species are primarily found in less deforested and impacted landscapes. Other studies performed in larger and protected Atlantic Forest patches also found elevated richness of high-sensitivity species, corroborating our assumption (e.g., more than 15 forest high-sensitivity species were reported in Develey and Martensen, 2006;Cavarzere et al, 2009;Antunes et al, 2013). This condition may explain the lack of relationship between Parker's high-sensitivity species and the variation of forest environmental conditions in more disturbed landscapes.…”
Section: Localsupporting
confidence: 90%
“…Even though we found the same result, we observed that the species we documented in this category encompass forest species very common in disturbed sites (e.g., Patagioenas picazuro, Tangara cayana, Brotogeris chiriri, Tolmomyias sulphurescens, Icterus pyrrhopterus), even urban zones (e.g., Franz et al, 2010;Cruz and Piratelli, 2011;Alexandrino et al, 2013), but also include some species naturally considered more vulnerable to habitat loss and fragmentation, such as endemic (e.g., Automolus leucophthalmus, Conopophaga lineata, Drymophila ferruginea, Mackenziaena severa) and near-threatened and threatened species (e.g., the near threatened species Amazona aestiva, Antilophia galeata, Campephilus robustus, Leptodon cayanensis and Penelope superciliaris, the vulnerable species Cyanoloxia brissonii, and the endangered species Lanio penicillatus). These last are mainly reported in large and preserved patches (e.g., Anjos, 2006;Develey and Martensen, 2006;Cavarzere et al, 2009;Antunes et al, 2013). Thus, we noticed that the existing relationship between the richness of Parker's medium-sensitivity level and our measurement of forest environmental conditions (i.e., the rank of ecosystem service provisioning from Ferraz et al, 2014) has occurred in our study area only by the presence of these listed species.…”
Section: Localmentioning
confidence: 99%
“…In evaluating the richness of birds reported to EESA, it is observed a higher number of species recorded in relation to several areas of the Cerrado (see Valadão 2012), as well as several other protected areas in Brazil (Motta-Junior et al 2008, Cavarzere et al 2009, Aleixo and Guilherme 2010, with methodological reservations. Its expressive number of species places EESA among the richest protected areas in terms of bird species in Brazil (Pacheco et al 2007, Pinheiro and Dornas 2009, Somenzari et al 2011, especially in terms of areas not primarily covered by forest.…”
Section: Discussionmentioning
confidence: 99%
“…Para Bauru e região, nenhum registro havia sido documentado antes. O registro mais próximo da espécie situa-se no município de Gália, localizado a aproximadamente 220 km do corredor da Serra do Mar (Cavarzere et al, 2009). Outras cidades no interior do Estado de São Paulo com registros de P. koeniswaldiana são Itirapina (Willis, 2003), Anhembi (Antunes, 2005) e São Carlos (Motta-Júnior, 2006), todos realizados em fragmentos florestais acima de 100 ha.…”
Section: Resultsunclassified